Let d(x) = 2x - 4
Or
y = 2x - 4
We have replace x = y
x = 2y - 4
Now Isolate "y"
x + 4 = 2y
Pass "2" dividing
(x + 4) / 2 = y
y = x/2 + 2
Or
d(x)^-1 = x/2 + 2
Answer:
The other leg X = 8m
Step-by-step explanation:
As per Pythagorean theorem-
Square of hypotenuse = sum of square of other two sides of the triangle
Substituting the given values in above equation, we get -
m
The other leg X = 8m
9514 1404 393
Answer:
14
Step-by-step explanation:
Use the formula with n=3.
h(3) = h(3-2) +h(3-1)
h(3) = h(1) +h(2)
h(3) = -6 +20 . . . . . substitute the given values
h(3) = 14
Answer: Nope, she is 29 and still alive
Step-by-step explanation: